Research Productivity and the Quality of Interregional Knowledge Networks. - Sebestyén, Tamás; Varga, Attila (PTE KTK Műhelytanulmányok, 2022)
This paper estimates the impact of interregional knowledge flows on the productivity of research at the regional level. We develop the novel index of ’ego network quality’ in order to measure the value of knowledge that can be accessed from a particular region’s global knowledge network. Quality of interregional knowledge networks is related to the size of knowledge accumulated by the partners (‘knowledge potential’), the extent of collaboration among partners (‘local density’) and the position of partners in the entire knowledge network (‘global embeddedness’). Ego network quality impact on the productivity of research in scientific publications and patenting at the regional level is tested with co-patenting and EU Framework Program collaboration data for 189 European NUTS 2 regions.